A Case of Low Rectovaginal Fistula of Obstetric Origin: Treatment by Fistulotomy and Reconstitution or Advancement Flap? - Elroy Patrick Weledji; Felix Adolphe Elong; Divine Enoru Eyongeta (Frontiers in Surgery, 2020)
Many small low rectovaginal fistulas represent incompletely healed (third degree) perineal lacerations i. e., involving the sphincters. An individualized, systematic approach to these fistulas based on their size, location, and etiology provides a more concise treatment plan. We report a case of a low rectovaginal fistula developed some years following forceps vaginal delivery. This was managed successfully by a fistulotomy in which the bridge of skin and scar tissue was divided, and the defect repaired as a classical third degree perineal laceration. On the background of coexisting or occult sphincter damage which usually follows obstetric trauma, a fistulotomy and immediate composite repair for small, low rectovaginal fistula may be advantageous and acceptable in a low resource setting where endoanal imaging and manometry are not available.